2011
DOI: 10.4311/jcks2009es0108
|View full text |Cite
|
Sign up to set email alerts
|

Subglacial Maze Origin in Low-Dip Marble Stripe Karst: Examples from Norway

Abstract: Maze caves or network caves are enigmatic in their evolution, as they form flow nets rather than more efficient, direct point-to-point flow routes. Network caves are often characterized by uniform passage dimensions in several directions, which indicates simultaneous dissolution of most available fractures. Nonshauggrotta in Gildeskål, northern Norway, is formed in low-dip marble strata and situated as a relict in a topographical and hydrological hanging position, thus lacking a modern drainage area. The cave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Carbonate sedimentary formations including more than 75% of carbonate minerals such as limestone and dolomite, are the most important karstifiable rocks (Ford and Williams 2007). Karst also occurs in other rock types with predominantly carbonatic composition, including carbonatic conglomerates (Goeppert et al 2011) and carbonatic metamorphic rocks (marble, calcite schist; Skoglund and Lauritzen 2011). Evaporitic formations, such as gypsum and anhydrite, are also highly karstifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate sedimentary formations including more than 75% of carbonate minerals such as limestone and dolomite, are the most important karstifiable rocks (Ford and Williams 2007). Karst also occurs in other rock types with predominantly carbonatic composition, including carbonatic conglomerates (Goeppert et al 2011) and carbonatic metamorphic rocks (marble, calcite schist; Skoglund and Lauritzen 2011). Evaporitic formations, such as gypsum and anhydrite, are also highly karstifiable.…”
Section: Introductionmentioning
confidence: 99%
“…The functioning of the karst system is a widely studied field (cf., e.g., Bauer and Tóth (2015)). Veneziano and Essiam (2003) have shown that for an aquifer with a multifractal hydraulic conductivity field, the resulting hydraulic gradient and specific discharge are also multifractal fields; see also (Florea 2001;Skoglund and Lauritzen 2011). Hence, an analysis focusing on the fractal or multifractal characteristics of the discharge of springs may shed light on certain properties of the karst media that would otherwise be difficult to infer directly.…”
Section: Similar Approaches In the Literaturementioning
confidence: 99%
“…Good examples of karst fractals are: the karst landscape densely dotted by craters and karst depressions, often overlapping each other, the corroded walls in caves covered by micro-forms, the rock massifs cut by nets of karsified fissures, and others structures. The problem is not discussed in details in scientific literature, there are only a few works devoted to fractal problematics in karst (Curl 1986, Laverty 1987, Kusumayudha et al 2000, Finnesand, Curl 2009, Piccini 2011, Skoglund, Lauritzen 2011.…”
Section: Introductionmentioning
confidence: 99%